Galaxy Zoo: comparing the demographics of spiral arm number and a new method for correcting redshift bias - Hart, Ross E.; Bamford, Steven P.; Willett, Kyle W.; Masters, Karen L.; Cardamone, Carolin; Lintott, Chris J.; Mackay, Robert J.; Nichol, Robert C.; Rosslowe, Christopher K.; Simmons, Brooke D.; Smethurst, Rebecca J. (Oxford University Press, 2016)
The majority of galaxies in the local Universe exhibit spiral structure with a variety of forms. Many galaxies possess two prominent spiral arms, some have more, while others display a many-armed flocculent appearance. Spiral arms are associated with enhanced gas content and star formation in the discs of low-redshift galaxies, so are important in the understanding of star formation in the local universe. As both the visual appearance of spiral structure, and the mechanisms responsible for it vary from galaxy to galaxy, a reliable method for defining spiral samples with different visual morphologies is required. In this paper, we develop a new debiasing method to reliably correct for redshift-dependent bias in Galaxy Zoo 2, and release the new set of debiased classifications. Using these, a luminosity-limited sample of ∼18 000 Sloan Digital Sky Survey spiral galaxies is defined, which are then further sub-categorized by spiral arm number. In order to explore how different spiral galaxies form, the demographics of spiral galaxies with different spiral arm numbers are compared. It is found that whilst all spiral galaxies occupy similar ranges of stellar mass and environment, many-armed galaxies display much bluer colours than their two-armed counterparts. We conclude that two-armed structure is ubiquitous in star-forming discs, whereas many-armed spiral structure appears to be a short-lived phase, associated with more recent, stochastic star-formation activity.